Upgrade : [large type] a novel - Crouch, Blake (Random House Large Print, 2022)
"An ordinary man undergoes a startling transformation-and fears that all of humanity may be next-in the mindblowing new thriller from the New York Times bestselling author of Dark Matter and Recursion Logan Ramsay can feel his brain...changing. And his body too. He's becoming something other than himself. Maybe even something other than human. As he sets out to discover who did this to him, and why, his transformation threatens everything-his family, his job, even his freedom. Because the truth of what's happened to him is more disturbing than he could possibly imagine. His DNA has been rewritten with a genetic-engineering breakthrough beyond anything the world has seen-one that could change our very definitions of humanity. And the battle to control this unfathomable power has already begun. But what if humankind's only hope for survival lies in embracing this change-whatever the cost? Which side will Logan take? And by the time it's over, will he-and the people he loves-even recognize him? Upgrade is a stunningly inventive, ferociously plotted science-fiction thriller that explores the limits of our humanity-and asks what's at risk when technology lets us reengineer not just the world around us, but ourselves"--